SUPREMASI YESUS DI ERA POSTMODERN: MENELUSURI KRISTOLOGI ATHANASIUS DALAM TEORI DAN PRAKSIS - Anggi Maringan Hasiholan (Bethel Press, 2023)
This article provides a brief overview of the reception of the theory and practice of Athanasian Christology in the postmodern era. As the Apostle defending the Council of Nicaea, Athanasius's thoughts and practice are worth exploring, especially regarding his soteriology and Christology. This research examines Athanasius' Christology and soteriology to be implemented for Christianity in the postmodern era. The research method used is descriptive qualitative with a historical approach. The research results show that Athanasius viewed humans as initially created in a right relationship with God, but sin separated humans from God. Man fell into a state of sin and destruction and lost his actual life and genuine relationship with the Creator. However, a loving God sent His Son, Jesus Christ, to restore and save humanity. This is where the Logos of God works in humanity's creation, preservation, and salvation. Athanasius's concept influenced the church's concept of salvation today, and the impact of Athanasius's thought became a reference for the church in the doctrine of salvation. In internalization for postmodern society, four steps can be taken, namely (i) clarity, (ii) credibility, (iii) reasonable, and (iv) intimacy.